Calcarisporium cordycipiticola sp. nov., an important fungal pathogen of Cordyceps militaris - Sun, Jing-Zu; Dong, Cai-Hong; Liu, Xing-Zhong; Liu, Jian-Kui; Hyde, Kevin D. (Phytotaxa, 2016)
Production of the medicinal and edible fungus Cordyceps militaris has dramatically increased in China because of its alleged medicinal properties. During industrial production, a fungal parasite was found to infect the fruiting bodies causing significant quality and yield losses. Two isolates were obtained from fruiting bodies of C. militaris in Beijing and Shanghai mushroom farms and were characterized by morphological and phylogenetic analyses of SSU and ITS sequence data. The phylogenetic analyses showed that they belong to the genus Calcarisporium and are related to the type species, C. arbuscula with 91% ITS sequence similarity. We introduce this taxon as Calcarisporium cordycipiticola sp. nov., and compare it morphologically with other taxa in the genus. The interaction between this taxon, its host, and methods to control this fungicolous taxon need further studies.